Advanced Virgo phase cameras. Issue 7 (May 2016) - van der Schaaf, L; Agatsuma, K; van Beuzekom, M; Gebyehu, M; van den Brand, J
Abstract: A century after the prediction of gravitational waves, detectors have reached the sensitivity needed to proof their existence. One of them, the Virgo interferometer in Pisa, is presently being upgraded to Advanced Virgo (AdV) and will come into operation in 2016. The power stored in the interferometer arms raises from 20 to 700 kW. This increase is expected to introduce higher order modes in the beam, which could reduce the circulating power in the interferometer, limiting the sensitivity of the instrument. To suppress these higher-order modes, the core optics of Advanced Virgo is equipped with a thermal compensation system. Phase cameras, monitoring the real-time status of the beam constitute a critical component of this compensation system. These cameras measure the phases and amplitudes of the laser-light fields at the frequencies selected to control the interferometer. The measurement combines heterodyne detection with a scan of the wave front over a photodetector with pin-hole aperture. Three cameras observe the phase front of these laser sidebands. Two of them monitor the in-and output of the interferometer arms and the third one is used in the control of the aberrations introduced by the power recycling cavity. In this paper the working principle of the phase cameras is explained and some characteristic parameters are described.